Menggali Dampak Sosial Dan Ekonomi Dari Permasalahan Pinjaman Online Dalam Industri Financial Technology di Kabupaten Bekasi - Ayu Kartika Agustin; Febiola Siska Wulandari; Desinta Sari (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This article explores the social and economic impacts of online lending issues in the Financial Technology industry. Through an in-depth review of factors such as poverty, over-indebtedness, and the role of technology in financial transformation, this article delves into the complex implications of this phenomenon. Considering the perspectives of consumers, regulators, and industry players, we explore the challenges and opportunities associated with addressing these online lending issues. This analysis provides valuable insights for stakeholders in developing policies and sustainable solutions to support the positive development of the Financial Technology industry. This research will use a qualitative approach to explore the social and economic impacts of online loans in the Financial Technology industry in Bekasi Regency.